Chromatic‐Third Relations in the Music of Bruckner: a Neo‐Riemannian Perspective. (15th May 2013) - Ramirez, Miguel
Abstract The present study offers an extended neo‐Riemannian examination of chromatic‐third relations in selected Bruckner compositions of the 1880s, and it constitutes the first such examination of the composer's music. Owing to its inherent indifference towards the notions of tonal centre and conventional harmonic syntax, a neo‐Riemannian transformational model seems particularly apt for the analysis of the music selected – music in which non‐functional chord progressions, symmetrical divisions of the octave and the temporary suspension of tonic centricity are featured. The characteristics of the works analysed here suggest an evolution in Bruckner's handling of chromaticism, from the seemingly sui generis mixture of plagal and chromatic‐third relations in the coda of the opening movement of the Sixth Symphony, to a more methodical use of hexatonic‐polar transformations in the motet Ecce sacerdos magnus, to the exhaustive, almost systematic exploration of hexatonic cycles in the finale of the Eighth Symphony.